Is early always better? Assessing soybean planting date in Minnesota - Potter, Bruce; Cerrudo, Aníbal Alejandro; Naeve, Seth (Wiley, 2025)
Planting date significantly impacts soybean (Glycine max L.) production in the Upper Midwest. Farmers often plant as early as possible, assuming higher risks and costs, to maximize yield potential. However, in drought-prone, low-productivity areas, the benefits of early planting, which are attributed to radiation utilization, could be offset by water stress. This study evaluated the effects of planting date and cultivar maturity on yield across environments with varying attainable productivity levels. Field experiments were conducted over 25 consecutive seasons (1999–2023) in Lamberton, Southwest MN, encompassing a broad range of productivity. An attainable productivity index that was strongly linked to precipitation availability was used to classify environments. In high-attainable productivity environments, early planting with full-season cultivars resulted in significant yield advantages, with delays reducing yield by up to 0.3% per day. Conversely, in low-productivity environments, planting delays until late May did not reduce yield and, in extreme cases, yielded positive responses. Across all the environments, planting beyond the end of May consistently led to steep yield declines above 1% per day, regardless of resource availability or maturity. These findings highlighted that early planting with full-season cultivars was optimal for high-productivity environments but provided no clear yield advantage in drought-prone, low-productivity environments, where the risks and costs may not be justified. The results could offer guidance for tailoring planting date within heterogeneous fields.